Burden of arrhythmias and associated in-hospital mortality in acute decompensated diabetes mellitus. Issue 5 (8th May 2021) - Patel, Upenkumar; Desai, Rupak; Munshi, Rezwan; Patel, Palakkumar; Makaryus, Amgad N.
Abstract: To gain understanding of the burden of cardiac arrhythmias in patients with acutely decompensated diabetes mellitus (ADDM) on a large scale, we reviewed data on ADDM patients and subtypes of arrhythmias from the National Inpatient Sample from 2010 to 2014. The frequency and prevalence of cardiac arrhythmias were measured, as well as outcomes. Among 874, 107 hospitalized ADDM patients identified, 87, 970 (10.1%) developed arrhythmias. The ADDM-arrhythmia cohort showed higher all-cause mortality (1.4% vs 0.3%; adjusted odds ratio 2.58, 95% confidence interval 2.39–2.79, P < 0.001), prolonged hospital stays (4.2 ± 4.8 vs 3.3 ± 3.4 days), and higher hospital charges (32, 609 vs 23, 741) compared to those without arrhythmias ( P < 0.001). The prevalence of supraventricular arrhythmia (atrial fibrillation, supraventricular tachycardia, and atrial flutter) and ventricular arrhythmia (ventricular tachycardia and ventricular fibrillation) was 2965 and 446 per 100, 000 ADDM-related hospitalizations, respectively. The prevalence of any arrhythmias and atrial fibrillation in ADDM patients increased by 20.4% and 38.1%, respectively. The highest increase in the prevalence of arrhythmia among ADDM patients was observed in adults aged 18 to 44 years (22.5%).